A Comparison and Cost Analysis of Cranioplasty Techniques. Issue 1 (January 2015) - Gilardino, Mirko S.; Karunanayake, Mihiran; Al-Humsi, Taghreed; Izadpanah, Ali; Al-Ajmi, Hasan; Marcoux, Judith; Atkinson, Jeffrey; Farmer, Jean-Pierre
<x xml:space="preserve">Abstract</x> Background Cranioplasty can be performed either with gold-standard, autologous bone grafts and osteotomies or alloplastic materials in skeletally mature patients. Recently, custom computer-generated implants (CCGIs) have gained popularity with surgeons because of potential advantages, which include preoperatively planned contour, obviated donor-site morbidity, and operative time savings. A remaining concern is the cost of CCGI production. The purpose of the present study was to objectively compare the operative time and relative cost of cranioplasties performed with autologous versus CCGI techniques at our center. Methods A review of all autologous and CCGI cranioplasties performed at our institution over the last 7 years was performed. The following operative variables and associated costs were tabulated: length of operating room, length of ward/intensive care unit (ICU) stay, hardware/implants utilized, and need for transfusion. Results Total average cost did not differ statistically between the autologous group (n = 15; 25, 797.43) and the CCGI cohort (n = 12; 28, 560.58). Operative time (P = 0.004), need for ICU admission (P < 0.001), and number of complications (P = 0.008) were all statistically significantly less in the CCGI group. The length of hospital stayand number of cases needing transfusion were fewer in the CCGI group but did not reach statistical significance. Conclusion The results of the present study demonstrated no significant increase in overall treatment cost associated with the use of the CCGI cranioplasty technique. In addition, the latter was associated with a statistically significant decrease in operative time and need for ICU admission when compared with those patients who underwent autologous bone cranioplasty. Level of evidence: IV, therapeutic